Effects of clinical Pilates on the fitness in people with children with disabilities: a randomized controlled trial - Senturk, Yazgi; Kirmizigil, Berkiye; Tuzun, Emine H. (Future Medicine Ltd, 2021)
Aim: This study aimed to examine the effects of Clinical Pilates Exercises (CPE) on Health-Related Physical Fitness in Primary Caregivers. Patients & methods: Fifty-five participants were randomly divided into the CPE group and the Control group. Individuals in the CPE group performed CPE two-times a week for 8 weeks. Results: The intergroup comparisons showed that there were significant differences in favor of the CPE group in the sit-up test, body extension endurance, body flexion endurance, side bridge (right), squat test and flexibility tests (p < 0.05). The intragroup comparisons revealed significant differences in the CPE group in the sit-up test, body flexion endurance, side bridge (both sides), squat test and flexibility tests (p < 0.05). Conclusion: CPEs are effective on improvement of health-related fitness parameters in the primary caregivers of children with disabilities.
Keywords: children with disabilities; clinical Pilates; exercise; parent; physical fitness